A global worldwide VLBI network to strengthen the celestial reference frame at K band for ICRF4 - Charlot, P. (2025)
The next realization of the International Celestial Reference Frame, namely ICRF4, is planned for 2027. Like its predecessors, the frame will be built by a working group of the IAU that was formed in 2021 for this purpose. A novel feature of ICRF4 is that it will be multi-waveband, meaning that it will include an optical component (based on the Gaia Data Release 4 data) besides the three radio components (at the S/X, K and X/Ka frequencies) that were the basis of ICRF3. The issues involved in generating such a multi-waveband frame have been investigated by the working group and are discussed in. At the same time, the VLBI observing programs are being strengthened to correct previous deficiencies and improve over ICRF3. At K band, a large worldwide VLBI network consisting of the Very long Baseline Array (in the United States), the European VLBI Network (which includes telescopes in Europe, South Africa, China and South Korea), and antennas in Australia, has been assembled, for a total of up to 27 telescopes, with correlation to be carried out at the Joint Institute for VLBI ERIC. The aim of the project is threefold: (i) (i) increase the intrinsic source position precision by observing with longer baselines than achieved so far, (ii) reduce the North-South asymmetry of the frame by incorporating long baselines between South Africa and Europe and between Australia and Asia, and (iii) image the sources at high resolution and with high dynamic range. A total of 10 observing epochs (to take place before 2027), each 24-hour long, have been granted to cycle over the 1200 sources in the frame and achieve these goals. The presentation will give an overview of the program and discuss initial results according to availability.